Evaluasi Dampak Program Peningkatan Kompetensi Pendidik Dan Tenaga Kependidikan Paud Di Ibu Kota Nusantara - Heppy Liana; Baequni; Aminah; Yeni Aslina (Manajemen Pendidikan Program Doktor, 2025)
The program to enhance the competencies of educators and educational personnel in Early Childhood Education (PAUD) through a partnership scheme in the Capital City of Nusantara (IKN) represents a strategic initiative of the Ministry of Education, Culture, Research, and Technology aimed at preparing PAUD institutions to become learning organizations capable of serving as disseminating partners for surrounding PAUD units. This study aims to analyze the impact of the partnership program on improving the competencies of PAUD educators and heads of institutions, as well as to identify the impacts perceived by parents through an exploration of the perspectives of teachers, parents, and children. This study employed an evaluative research design using the Responsive Stake Evaluation Model, which emphasizes the components of antecedents, transactions, and outcomes. Research participants were selected through purposive sampling, involving heads of PAUD institutions, educators, parents, and children across six sub-districts in the IKN area, covering Penajam Paser Utara Regency and Kutai Kartanegara Regency. Data were collected through observation, interviews, and documentation, and were analyzed using descriptive qualitative methods. The findings indicate that the partnership program had a significant impact on enhancing the competencies of PAUD educators, particularly in fostering reflective teaching practices, implementing learning strategies aligned with the characteristics of early childhood learners, and developing participatory learning environments. Educators demonstrated a paradigm shift toward child-centered, contextual, and inclusive learning. In addition, the competencies of PAUD heads were also strengthened, especially in the development of participatory learning environments and collaborative, reflective instructional leadership. The program’s impact was also perceived by parents through increased involvement in the learning process and improved communication with schools, which contributed to more optimal child development. The success of the program was supported by synergy among partner PAUD institutions, facilitators, local governments, higher education institutions, and the Teacher Development Center (Balai Guru Penggerak), positioning the partnership program as a sustainable model for PAUD competency development in the IKN region.